Cement-treated recycled glass and crushed rock blends: modulus of rupture and stiffness properties. Issue 3 (23rd February 2022) - Arulrajah, Arul; Maghool, Farshid; Newman, Graeme; Haghighi, Hamed; Horpibulsuk, Suksun
ABSTRACT : Recycled waste materials are increasingly being used as low carbon construction materials in civil infrastructure works, as recycled materials have significant carbon savings compared with virgin quarried materials. In this research, the stiffness and modulus of rupture properties of crushed rock (CR) blended with recycled glass (RG) were evaluated. The engineering properties of the four cement-treated CR/RG blends evaluated were: 100% CR100 (100CR), 90% CR with 10% RG (CR90/RG10), 80% CR with 20% RG (CR80/RG20), 70% CR with 30% RG (CR70/RG30). 3% dosage of general blend (GB) cement was used in all the RG/ CR blends. The results indicated that cement-treated RG/CR blends, with up to 20% RG, are suitable as pavement subbase materials. Unconfined compression strength (UCS) values met the minimum requirement for 7 days of curing for all the CR/RG blends. The results of repeated load triaxial (RLT) tests and flexural beam tests were found to be within the ranges reported for the previous testing on other accepted recycled and quarry products. Based on this laboratory assessment, RG can be recommended for incorporation as a supplementary material in cement-treated CR pavement applications, which will increase the uptake of recycled products as a civil engineering construction material.